Medication Adherence Among Ambulatory Patients With Type 2 Diabetes in a Tertiary Healthcare Setting in Southwestern Nigeria (2011)
Objective: To assess adherence to medication among ambulatory patients with type 2 diabetes, ascertain the level of glycemic control, and evaluate patients’ opinions on probable reasons for nonadherence with a view to identify areas of intervention to improve adherence. Methods: A prospective cross-sectional study was carried out at a 900-bed tertiary teaching hospital in Ibadan, Southwestern Nigeria between June and August, 2009. Out of 140 consented patients, 114 (81.4%) properly responded to the validated and pre-tested data collection tool and these were subsequently considered for analysis. Descriptive statistics were used to summarize the data. Means and proportions were compared using student t-test and chi-square or Kruskal-Wallis test as appropriate, with p<0.05 considered statistical significant. Results: Approximately sixty percent of the patients were adjudged adherent with prescribed medication. Out of 58.8% of the cohort who gave their recent fasting plasma glucose (FPG) values, 59.7% had FPG above 110mg/dL. The mean FPG for patients was 139.05 (SD=70.5)mg/dL, males and females significantly differed in their mean FPG, 146.55 (SD=85.0)mg/dL versus 133.33 (SD=57.6)mg/dL respectively (p=0.032). Also, the mean FPG values for adherent patients, 137.09 (SD=59.3)mg/dL was lower than their non-adherent counterparts, 143.92 (SD=87.6) mg/dL, but the difference was not statistically significant (p=0.095). Financial constraint (34.4%) was the major barrier to optimal adherence with medication. A significant association exist between genders and opinions on physician’s mode of approach during patientphysician interaction as a contributory factor for non-adherence (p=0.038). Conclusion: Medication adherence of ambulatory type 2 diabetes patients is considerable. However, the relatively high level of adherence did not appear to have significantly impacted on patients’ glycemic status due to a substantial number who had plasma glucose above the recommended targets. Multiple *Rasaq ADISA. B.Pharm, M.Pharm. Lecturer 1. Department of Clinical Pharmacy &Pharmacy Administration, Faculty of Pharmacy, University of Ibadan (Nigeria). Titilayo O. FAKEYE. B.Pharm, M.Sc, PhD. Senior Lecturer. Department of Clinical Pharmacy &Pharmacy Administration, Faculty of Pharmacy, University of Ibadan (Nigeria). Adesoji FASANMADE. MBBS, FWACP. Consultant endocrinologist. Department of Medicine, Endocrinology unit, College of Medicine, University of Ibadan, (Nigeria). methods may be required to detect patient who report adherence but who may in fact be nonadherent. Also, adherence to other aspects of diabetes management plan needs to be encouraged in order to accomplish optimal glycemic control. Initiatives targeting patient-specific intervention improve medication adherence should be considered.